258 The Interactions of Change in Nutrition on Uterine Environment and Plasma Cholesterol Concentrations in Beef Cattle. (7th May 2021) - Andrews, Taylor; Epperson, Kaitlin; Rich, Jerica; Zoca, Saulo Menegatti; Zezeski, Abigail L; Geary, Thomas W; Lawrence, Rhea D; Walker, Julie; Perry, George
Abstract: The objective was to evaluate the impact of nutritional changes prior to and after artificial insemination (AI) on uterine environment and plasma cholesterol concentrations. Beef heifers (n = 79) were randomly assigned to two dietary treatment groups (High=155% or Low=86% of maintenance energy) for 30 d prior to AI (pre-AI). At AI, heifers were randomly assigned new treatment groups (post-AI) which created four pre- x post-AI diet treatments (High-High, High-Low, Low-High, and Low-Low). Post-AI dietary treatments continued until uteri were flushed for embryo recovery (d 7 or 8 post-AI). Blood samples were collected on d -3, -2, -1, 0 (AI day), 1, 3, 5, 7, and 8 for analysis of plasma cholesterol concentrations using a colorimetric assay. Uterine flushes were analyzed for concentrations of Mg, Al, P, S, K, Ca, Cu, Zn, Se, and Fe by ICPMS. Plasma cholesterol (repeated measures) and uterine mineral concentrations were analyzed using the MIXED procedures in SAS. Plasma cholesterol concentrations changed over time (P < 0.0001); however, there were no differences between treatments (P > 0.10). There was an effect of embryo presence on uterine flush mineral concentrations for Mg (P < 0.04), Al (P < 0.01), S (P < 0.01), K (P < 0.01), and Ca (P < 0.01), with decreased concentrations when uterine flushes contained an embryo. There was no effect of pre-AI diet on mineral concentrations; however, there was an effect of post-AI diet on S (P < 0.02) and Ca (P = 0.03). High diet heifers had increased S and Ca concentrations compared to low diet heifers. Sulfur concentration was affected by a pre-AI diet by embryo interaction (P < 0.03). There was a post-AI by embryo interaction on P (P < 0.03), Zn (P = 0.02), and Se (P = 0.02). Also, there was a pre-AI by post-AI by embryo interaction on Mg (P < 0.05). In conclusion, changing plane of nutrition pre- and post-AI had no effect on plasma cholesterol concentrations; however, presence of an embryo affected uterine mineral concentrations.